Estimação de parâmetros de demanda e oferta em mercados de produtos diferenciados - Moraes, Flávio Luiz Alves Flores de (2008)
The purpose of this paper is to discuss in details the development of estimation methods of demand and supply parameters in differentiated products markets. The techniques presented consider explicitly the endogeneity of prices and can be applied to different types of industries. The market demands system is derived from discrete choice models describing the behaviour of the consumer. This system is then combined with hypothesis about the cost functions and the behaviour of price determination by the Örms to generate equilibrium prices and quantities. The parameters to be estimated are those that determine the marginal costs of the firms and the distribution of the consumersí tastes. This distribution determine elasticities and these, combined with the marginal cost and a hypothesis of Nash equilibrium, determine equilibrium prices. These elasticities and cost parameters play a central role in analysis of descriptive